2014
DOI: 10.1377/hlthaff.2013.1303
|View full text |Cite
|
Sign up to set email alerts
|

High Levels Of Bed Occupancy Associated With Increased Inpatient And Thirty-Day Hospital Mortality In Denmark

Abstract: High bed occupancy rates have been considered a matter of reduced patient comfort and privacy and an indicator of high productivity for hospitals. Hospitals with bed occupancy rates of above 85 percent are generally considered to have bed shortages. Little attention has been paid to the impact of these shortages on patients' outcomes. We analyzed all 2.65 million admissions to Danish hospitals' departments of medicine in the period 1995-2012. We found that high bed occupancy rates were associated with a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 22 publications
1
71
1
1
Order By: Relevance
“…53,54 Thirty studies analyzed the association between capacity strain and mortality. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][32][33][34][35][36][37][38][39][40][41][42][43]48,49,53 All observational studies were cohort studies; all but four were retrospective. 32,42,43,46 Eight studies described interventions to improve care during times of capacity strain, [55][56][57][58][59][60][61][62] none using randomization to assign treatment category.…”
Section: Resultsmentioning
confidence: 99%
“…53,54 Thirty studies analyzed the association between capacity strain and mortality. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][32][33][34][35][36][37][38][39][40][41][42][43]48,49,53 All observational studies were cohort studies; all but four were retrospective. 32,42,43,46 Eight studies described interventions to improve care during times of capacity strain, [55][56][57][58][59][60][61][62] none using randomization to assign treatment category.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a Danish study recently demonstrated how high bed occupancy rates were associated with increased inpatient and 30-day mortality. 28 Improved risk assessment may help identify patients suitable for outpatient treatment and thus decrease bed occupancy. Our study shows that a low suPAR can identify patients with an even lower mortality than the average, who may be suitable for treatment outside the hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…10 11 "Boarding"-moving patients from emergency departments to corridors of wards that are full to help spread the burden-has been offered as a solution in the United Kingdom in the past couple of winters, but this approach fails to tackle the problem and is likely to compromise our ability to deliver dignified, high quality care within the hospital system. 12 There is a paucity of formal evidence in this controversial area, though.…”
Section: No-chris Whalementioning
confidence: 99%
“…12 13 We accept that crowding in emergency departments is hazardous, but we also need to recognise that crowding within the whole hospital is hazardous and that it hinders flow.…”
Section: "Pull" From the Communitymentioning
confidence: 99%